SYNTHESIS OF MANAGEMENT CONCEPTS FOR ORGANIC FARM NETWORKS COMMUNITY ENTERPRISES, CHANA DISTRICT, SONGKHLA PROVINCE - budmata, Narongrit; tongsri, Prachuap; luxchaigul, Nat (Journal of Social Science and Cultural, 2023)
This paper approach a synthesis of the management concepts of community enterprises in the organic farm networks, Chana District, Songkhla Province, by applying the Sufficiency Economy Philosophy to the community enterprise in the organic farm networks and activities to lesson learned and knowledge transfer in managing community enterprise groups, organic farm networks in the community. There is a practical application that create value and social benefits to the community conducted with the objective of management concept of community enterprise groups, organic farm networks, Chana District, Songkhla Province. In terms of group management to success strengthen for planning as follows: 1) Organizing process management system 2) Upgrading production standards for continuously sustainability 3) Creating cooperative activities for expanding networks 4) Marketing channels development along with product development in aspect dimensions of identity and management concept with the 4M principles, including Man, Money, Materials and Management as input factors. To analyzing the internal and external environment context of community enterprise group, SWOT analysis techniques were used and the quality management cycle (PDCA) consisted of 4 steps: Plan-Do-Check-Act. Efficiency and sustainable managing the group’s resources, in addition, the Community Enterprise Group of the Chana District, organic farm networks also approach to the Sufficiency Economy Philosophy as an important principle in quality of life and conserving the community’s natural resources for sustainability. To push the group operational goals towards stability, prosperity and sustainability of the community.